Pengaruh Kualitas Produk, E-Service Quality Dan Online Customer Reviews Terhadap Minat Beli Yellow Fit Kitchen - Vivian Vivian; Donant Alananto Iskandar (STREAMING, 2025)
This study aims to examine the influence of product quality, e-service quality, and online customer reviews on purchase intention toward Yellow Fit Kitchen products. A quantitative research approach was employed using SPSS Statistics 24 to analyze data collected from 105 respondents residing in Jakarta, Bogor, Bekasi, and other regions who were familiar with Yellow Fit Kitchen. The sample was selected using non-probability sampling with a purposive sampling technique. The findings reveal that product quality does not have a significant effect on purchase intention, whereas e-service quality and online customer reviews have positive and significant effects on consumers' purchase intention. These results indicate that consumers place greater importance on service quality and online reviews than product quality when considering Yellow Fit Kitchen products. The study provides practical implications for the company by highlighting the need to continuously improve its e-service quality and encourage positive customer reviews while maintaining product quality to strengthen its competitiveness and enhance consumers' intention to purchase.